Enzymes in Food Technology : Improvements and Innovations - Kuddus, Mohammed (Singapore : Springer Singapore : Imprint: Springer, 2018)
The integration of enzymes in food processing is well known, and dedicated research is continually being pursued to address the global food crisis. This book provides a broad, up-to-date overview of the enzymes used in food technology. It discusses microbial, plant and animal enzymes in the context of their applications in the food sector; process of immobilization; thermal and operational stability; increased product specificity and specific activity; enzyme engineering; implementation of high-throughput techniques; screening of relatively unexplored environments; and development of more efficient enzymes. Offering a comprehensive reference resource on the most progressive field of food technology, this book is of interest to professionals, scientists and academics in the food and biotech industries.
Enzyme immobilization methods and applications in food industry -- Cold-active enzymes in food processing -- Transglutaminase protein substrates of food interest -- Enhanced dyeing efficiency of enymatically modified protein fibers -- Tannin degrading enzymes: catalytic properties and technological perspectives -- Production of food enzymes from recombinant microorganisms -- Protein modification using ionic liquids: a comprehensive overview on their effects on activity, stability and applications of enzymes -- Application of enzymes in meat processing -- Chemoenzymatic bioconjugation of antibodies: linking proteins for biomedical applications -- Microbial enzymes in food biotechnology -- Epigallocatechin gallate glucosides: Enzymatic synthesizes to improve its biological activity -- Food enzyme and nanotechnology -- Abzymes in food biotechnology -- Enzymes as a food additives -- Enzymes in Animal Feed Industry.
Description based on publisher-supplied MARC data.
Keywords: Biochemical engineering; Food -- Biotechnology; Microbiology